Intermittent Self Dilation – An Option For The Prevention of Urethral Stricture Recurrence After Filliform Follower Urethral Dilation - Shrestha, N M (Journal of Nepalgunj Medical College, 2018)
Background: Urethral stricture and its recurrence is still a major problem in male. Several procedures are present for the treatment of the disease. Lapides introduced the concept of intermittent self dilatation (ISD) which has decreased the incidence of recurrence of urethral stricture if doing properly. The aim of the this study was to report the outcomes of ISD for the treatment of urethral stricture after Filliform follower urethral dilatation (FFUD). Method: This was a prospective comparative study, conducted in the department of surgery, urology unit from March 2013 to February 2016. Total of 49 patients were enrolled and were randomly divided into Group A and Group B. In Group A, all the patients were taught ISD with Nelaton Catheter after FFUD. In group B, all patients underwent only FFUD for urethral stricture. In both groups, Foley’s catheter was removed after 2 weeks of FFUD. These patients who had difficulty In passing urine or having lower urinary tract syndrome after removal of catheter, were evaluated for urethral stricture recurrency by clinical symptoms, ultrasonography, urine test for culture and sensitivity, cystoscopy/urethrogram as necessarily. Result: In Group A, 4 patients out of 20(20%)developed urethral stricture recurrency where as in Group B,18 patients out of 23 (78.26%) developed urethral stricture recurrency. Therefore, the rate of urethral stricture recurrence is significantly more in group B than the Group A (p< 0.001). Conclusion: ISD is an effective way for the prevention of urethtral stricture recurrence after FFUD. JNGMC, Vol. 14 No. 2 December 2016, Page: 38-40